THE INFLUENCE OF AUDIO LINGUAL METHOD AND EMOTIONAL QUOTIENT TOWARDS LISTENING ABILITY OF THE EIGHTH GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 4 LUBUKLINGGAU - Indawan Syahri; Tahrun Tahrun; Qorie Pratiwi (ELTE Journal (English Languange Teaching and Education), 2017)
The objectives of this study, among others are: (1) to reveal the difference of student’s ability to listen between those of the students who with the Audio Lingual Method and conventional teaching of the eighth grade students of SMP Negeri 4 Lubuklinggau;  (2) to reveal the difference of students’ ability to listen between those of high emotional quotient students and low emotional quotient students of the eighth grade students of SMP Negeri 4 Lubuklinggau; (3) to reveal the effects of the interaction between Audio Lingual Method and Emotional Quotient of the eighth grade students of SMP Negeri 4 Lubuklinggau. This study used an experimental method. The population this study was 240 students of the eighth grade students of SMP Negeri 4 Lubuklinggau in the school year 2016/2017. The sample of this study were two classes who were choosen through cluster random sampling. Experiment class comprised 30 students and control class comprised 30 students. The data were collected by listening test. The data were analyzed by means of descriptive statistics, normality, homogeneity, and hypotheses testing of SPSS version 23. From the research findings above, it can be concluded that there is not any significance influence of Audio Lingual Method and the Stduents’ Emotional Quotient In Listening Ability to the Eighth Grade Students’ at State School 4 of Lubuklinggau.Keywords: Audio Lingual Method, Emotional Quotient, Listening